Maternal Obesity: Effects on Mother and Baby - Asyraf Vivaldi Wardoyo; Agung Ikhssani (Journal of Maternal and Child Health Sciences (JMCHS), 2021)
Maternal obesity during pregnancy is a public health burden that may be the underlying cause of the growing adult obesity rate worldwide. Understanding the relationship between maternal obesity and fetal obesity will provide useful information for the management and prevention of maternal and infant morbidity. Maternal obesity can adversely affect fetal development. Maternal obesity has become one of the most common risk factors in obstetric practice. Obesity in pregnancy is usually defined as a Body Mass Index [BMI] of 30 kg/m2 or more at the first antenatal consultation. In the management of obese women, pre-pregnancy weight loss through lifestyle improvements, particularly through individualized dietary therapy, appears to be important. Counseling to support improvements in diet and physical activity is considered a first-line intervention. This literature review discusses maternal obesity and its effects on mother and baby